Efecto del Nitrógeno, Fósforo y Potasio en el crecimiento de la buba de puntos verdes en cacao - Jiménez Sáenz, E.; DIAZ R, R. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The effect of nitrogen, phosphorus and potassium, single or in combination, upon the growth of the green point gall and the cacao plant, was studied under greenhouse conditions. - It was found that nitrogen increased the fresh weight of the gall. This stimulant effect was linear and quadratic, and statistically significant at the 1 and 5% levels, respectively. Phosphorus and potassium did not have any effect on the growth of the gall. - With regards to the growth of the plant, nitrogen also had a stimulant effect, statistically significant at the 1% level, whereas the potassium effect was significant only at the 5% level. Phosphorus did not have any effect on the fresh weight of the plant. - None of the possible N, P and K interactions were found to be statistically significant.